Oppression in the Poetry of Ali Bin Al-Jahm: A Study in the Semiotics of Desires - Al-Thubaiti, Khalaf Bin Saad Bin Khalaf (Arts for Linguistic & Literary Studies, 2024)
This study endeavors to examine the theme of oppression within the poetry of Ali ibn al-Jahm, focusing on selected poetic works and employing a semiotic analysis of desires. Much of ibn al-Jahm’s poetry underscores the influence of oppression as a driving force behind its composition, whether stemming from imprisonment, advancing age, or societal disintegration. Particularly notable in the chosen poetic examples is the essential role of women in imbuing the verses with significance. Drawing upon the semiotic framework proposed by Greimas and Fontanille, the study is structured into an introduction and two main sections: one exploring the alignment with prevailing value systems, and the other contrasting these systems. The conclusion synthesizes key findings, highlighting how the pervasive force of oppression engenders a spectrum of emotions in the poet, including fear, anxiety, and heartbreak. Moreover, it underscores the role of societal norms in perpetuating oppression and emphasizes the pivotal role of women in shaping the textual landscape and its interpretation. Ultimately, the study underscores how conditions such as age, advancing years, and incarceration serve as potent catalysts for psychological oppression.